PENGARUH TOTAL ASSETS TURNOVER (TATO) DAN DEBT TO EQUITY RATIO (DER) TERHADAP RETURN ON EQUITY (ROE) PADA PT MATAHARI DEPARTEMEN STORE TBK PERIODE 2013-2022 - Nurariffia, Nitia; Jati, Waluyo (Journal of Research and Publication Innovation, 2024)
This research aims to analyze financial ratios in measuring financial performance at PT Matahari Department Store Tbk for the 2013-2022 period. This type of research is associative quantitative analysis and the data used in this research is secondary data, namely the financial report data of PT Matahari Department Store Tbk for 2013-2022. This research found that there is a significant influence between Total Assets Turnover (TATO) on Return on Equity (ROE) at PT Matahari Department Store, Tbk. This can be seen in the t test which shows a significance value of 0.02 < 0.05 and a calculated t value of 11.867 > 2.364. This shows that the more efficient the company is in managing its assets, the higher the profitability generated by the company. This research also found that there is a significant influence between Debt to Equity Ratio (DER) on Return On Equity (ROE) at PT Matahari Department Store Tbk for the period 2013 - 2022. It can be seen from the t test that the significance value is 0.00 and the t value calculated as 4,871 > 2,364. This shows that the higher the use of debt, the lower the profitability generated by the company due to the debt interest burden. And simultaneously, Total Asset Turnover (TATO) and Debt to Equity Ratio (DER) have a significant influence on Return on Equity (ROE) at PT Matahari Department Store Tbk. It can be seen in the F test that the significance value is 0.00 < 0, 05 and the F value obtained is 74.920 > 2.364.